Exergames for motor rehabilitation in older adults: an umbrella review - Reis, E.; Postolache, G.; Teixeira, L.; Arriaga, P.; Lima, M. L.; Postolache, O. (Physical Therapy Reviews, 2019)
Background: Exergames have been used as an innovative motor rehabilitation method with the main aim of improving motivation and exercise. As research interest in exergaming for rehabilitation is rapidly growing, a review of existing systematic reviews is important to synthesize the available evidence and provide recommendations. Objectives: In this article, we systematically synthesized the information from reviews that have examined the effects if exergames on different body movement parameters in older adults with and without specific pathologies. Method: Searches were conducted in Web of Science, Scopus, PsycARTICLES, PsycINFO, Psychology and Behavioural Sciences Collection, PubMed, SciELO, B-On and Google Scholar, articulating different terms and Boolean operators. Systematic reviews, meta-analysis and literature reviews published until May 2017 that investigated exergame interventions on physical outcomes, such as balance, gait, limb movements, muscle strength, in healthy and non-healthy older adults. Results: Based on prior reviews, exergaming, as a standalone intervention, has a positive effect on balance, gait, muscle strength, upper limb function, and dexterity. When compared to traditional physiotherapy, exergaming has at least similar effects on these outcomes. Many of the investigated studies indicated low methodological quality for the evaluation of the effects of exergames on different outcomes related to motor rehabilitation. Conclusions: Exergames could be used as a complement to traditional forms of motor rehabilitation, but future individual studies and reviews should follow more rigorous methodological standards in order to improve the quality of the evidence and provide guidelines for the use of exergames in motor rehabilitation.